2011
DOI: 10.1007/s11095-011-0618-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Reprogramming: A New Technology Frontier in Pharmaceutical Research

Abstract: Induced pluripotent stem cells via cellular reprogramming are now finding multiple applications in the pharmaceutical research and drug development pipeline. In the pre-clinical stages, they serve as model systems for basic research on specific diseases and then as key experimental tools for testing and developing therapeutics. Here we examine the current state of cellular reprogramming technology, with a special emphasis on approaches that recapitulate previously intractable human diseases in vitro. We discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…Pluripotent stem cell (hPSC)‐derived neural stem cells (hNSC) appear as one of the most promising source of human neurons for various biomedical applications, including drug discovery , disease modeling , and cell replacement therapies . Consequently, mass cell production has become a major goal in this field , calling for robustness and cost‐effectiveness, parameters that need to be optimized using rational and systematic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Pluripotent stem cell (hPSC)‐derived neural stem cells (hNSC) appear as one of the most promising source of human neurons for various biomedical applications, including drug discovery , disease modeling , and cell replacement therapies . Consequently, mass cell production has become a major goal in this field , calling for robustness and cost‐effectiveness, parameters that need to be optimized using rational and systematic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on human biology can address adverse reactions in humans, which were unnoticed in animal models [79]. Improved preclinical models can empower to access human biology.…”
Section: Complementary Approachesmentioning
confidence: 99%
“…The idea was to use stem cell-based assays for toxicity evaluation in heart, liver, muscle, skin, and nerves. Recently new methods and tools have been used to culture human cells, reprogram them to specific phenotype and perform clinical trials [79,80,81]. The study published by Cell Reports show that induced pluripotent stem cells (iPSCs) derived from patients with frontotemporal dementia were genetically corrected and converted to cortical neurons [82].…”
Section: Complementary Approachesmentioning
confidence: 99%
“…Retroviral vectors were used to induce the ectopic expression of the four defined transcription factors that initiated events that reactivated genes associated with pluripotency. These reprogrammed cells were, like ESCs, found to be able to contribute to the germ-line in chimeric mice [ 17 ], and were capable of forming teratomas containing tissues derived from the three main germ layers [ 8 ]. Subsequently, it was also shown that the overexpression of other combinations of transcription factors, such as combinations including Nanog or Lin28, could trigger cellular reprogramming [ 18 ].…”
Section: Cellular Reprogrammingmentioning
confidence: 99%
“…The discovery that somatic cells can be reprogrammed to form iPSCs, which share similar characteristics with ESCs, has expanded the prospect for development of cellular therapies for degenerative diseases [ 8 ]. iPSCs face less ethical controversy as compared to ESCs, and as patient-specific iPSCs can be generated from patients of most genotypes, it is easier to model a wide range of diseases with iPSCs.…”
Section: Introductionmentioning
confidence: 99%